Structural analysis of the active site architecture of the VapC toxin from Shigella flexneri. Issue 7 (7th April 2016) - Xu, Kehan; Dedic, Emil; Brodersen, Ditlev E.
ABSTRACT: The VapC toxin from the Shigella flexneri 2a virulence plasmid pMYSH6000 belongs to the PIN domain protein family, which is characterized by a conserved fold with low amino acid sequence conservation. The toxin is a bona fide Mg 2+ ‐dependent ribonuclease and has been shown to target initiator tRNA fMet in vivo . Here, we present crystal structures of active site catalytic triad mutants D7A, D7N, and D98N of the VapC toxin in absence of antitoxin. In all structures, as well as in solution, VapC forms a dimer. In the D98N structure, a Hepes molecule occupies both active sites of the dimer and comparison with the structure of RNase H bound to a DNA/RNA hybrid suggests that the Hepes molecule mimics the position of an RNA nucleotide in the VapC active site. Proteins 2016; 84:892–899. © 2016 Wiley Periodicals, Inc.